Influence of bony resorption on endodontic treatment - Holland, Roberto; Valle, German F.; Taintor, Jerry F.; Ingle, John I. (Elsevier, 1983)
This article discusses the influence of bony resorption as it relates to endodontic success. Little attention has been given the significance of this factor on prognosis. The use of calcium hydroxide as a means of obtaining a more favorable periapical environment is proposed. © 1983.